2020
DOI: 10.32665/james.v3i2.138
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Kemampuan Berpikir Kreatif Matematis Melalui Model Pembelajaran Experiential Learning Berbasis Zone of Proximal Development (Zpd)

Abstract: This research's background is the students' mathematical creative thinking abilities that are rarely of concern so that they are generally classified as low. This study aims to determine the Zone of Proximal Development Experiential Learning model's effect based on improving mathematical creative thinking skills. The design of this study uses the Quasi-Experimental Design form. This study's population were students of class VII SMP Negeri 19 Bandar Lampung with a sample of two experimental classes and one cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…The study undertaken by Harun et al (2022) focused on a preschooler's learning and examined four key components identified by Vygotsky: ZPD, interpersonal com-munication, cooperative learning, and social pedagogy. Expanding on the initial component, Ruswanda (2020) asserted that the ZPD is the intermediary stage between a preschooler's prospective abilities and their current level of performance. The preschooler's stage of development is demonstrated through their capacity to do assignments autonomously.…”
Section: Preschooler-teacher Engagement Of Pbl In Early Science Educa...mentioning
confidence: 99%
“…The study undertaken by Harun et al (2022) focused on a preschooler's learning and examined four key components identified by Vygotsky: ZPD, interpersonal com-munication, cooperative learning, and social pedagogy. Expanding on the initial component, Ruswanda (2020) asserted that the ZPD is the intermediary stage between a preschooler's prospective abilities and their current level of performance. The preschooler's stage of development is demonstrated through their capacity to do assignments autonomously.…”
Section: Preschooler-teacher Engagement Of Pbl In Early Science Educa...mentioning
confidence: 99%
“…Hal tersebut dapat terwujud melalui pembelajaran alternatif yang dirancang sedemikian rupa sehingga mencerminkan keterlibatan siswa secara aktif, salah satunya yaitu melalui model Experiential Learning (EL). Kolb (1984) Beberapa penelitian terkait penerapan model EL sudah dilakukan dan terbukti memberikan pengaruh positif terhadap kemampuan berpikir kreatif matematis (Kurniawati, dkk., 2019;Ruswanda, dkk., 2020;Sari, dkk., 2022). Pada penelitianpenelitian tersebut mengukur pada nilai akhir atau posttest siswa dan dibandingkan dengan nilai akhir siswa yang mengikuti pembelajaran secara konvensional, dan belum melihat dalam sudut pandang perbedaan peningkatan yang terjadi jika dibandingkan dengan pretest.…”
unclassified